التحليل النقدي للخطاب في سورة المدثر على أساس نظرية نورمن فركلاف - حیدري, علی; رحماني, عبدالرزاق (جامعة الوادي - university of Eloued, 2020)
التحليل النقدي للخطاب هو انشعاب من علم الاجتماع. فقد تطور وصار يستخدم في شتّى الفروع كالسياسة والفلسفة والتاريخ والعلوم الدينية والأدبية و. وهو يحلّل ظاهر الخطاب وباطنه والموقف الذي أدّى إليه. فقد اختار الباحثان نظرية نورمن فركلاف وهي النظرية الأهم بين نظريات التحليل النقدي للخطاب، وطبّقاها بالمنهج الوصفي التحليلي على سورة المدثر التي نزلت على النبي (صلّي الله عليه وآله وسلّم) في أوقات متقطعة، ثم قسّما التحليل كما يقسمه فركلاف إلی تحليل النص وممارسة الخطاب، الممارسة الاجتماعية. فإن هذا يظهر تغيير الحالات والمواقف التي تنزل بها الآيات وتكون متناسقة مع الوضع الذي يؤدي إلى نزول الآية. فقد تبين من تحليل النص أن كلّاً من الكلمات والجمل والعبارات تأتي دقيقة مشيرة إلى حالة الأشخاص والأشياء التي تلزمها عند نزول الآية. ثم تغيير أسلوب الخطاب في الآيات يدل على تغيير الحالات عند الأشخاص، فأحياناً يكون تغيير الجملة من الخبرية إلى الإنشائية بهدف التخويف والتهويل أو التعجب. كما أن الوضع الاجتماعي السائد على البيئة قد يؤثر على لحن الآيات التي تنزل مخاطبةً النبي (صلّي الله عليه وآله وسلّم) أو المشركين. The critical analysis of the discourse is a subset of sociology. It has been developed and used in various branches such as politics, philosophy, history, religious and literary sciences. It analyzes the appearance of the speech and its internal situation that led to it. The two researchers chose Norman Farclav's theorem, which is the most important theory among the theories of the critical analysis of the discourse, and applied it to the descriptive analytic approach to Surat Al-Moddather, which was revealed to the Prophet (PBUH) through fractional time. The analysis section is then divided into analysis of text and speech practice, social practice, similar to what Farclav did. This shows a change in the situations and attitudes through which the verses revealed to the prophet and are consistent with the situation leading to the descent of the ayah. Analysis of the text shows that both words, sentences and phrases come to a precise point to the situation of the people and things that are led to the verses descendent. Then the changing of the discourse style in the verses, indicates a change in situations of people. Also sometimes changing the sentence from informative to creative with the aim of intimidation, moderation or exclamation. In addition to that, the social situation prevailing in the environment may also affect the melody of the verses that descend to address the Prophet (PBUH) or the polythiests.
مقال
Keywords: سورة المدثر، التحليل النقدي للخطاب، نورمن فركلاف; Al-Moddather, Critical analysis of the Speech, Norman Farclav.